Dynamic subsumption architecture for programming intelligent agents - Nakashima, H.; Noda, I. (International Conference on Multi Agent Systems : Cite des Sciences-la Villette, Paris, France, July 3-7, 1998 : proceedings, 1998)
This paper describes the application of an organic programming language Gaea in programming complex and flexible multi-agent systems. We consider a soccer game as an example. Using organic programming, we can program soccer players in an extended version of a subsumption architecture, called a dynamic subsumption architecture, which is more flexible and efficient than the original one.